COVID-19 patients share common, corticosteroid-independent features of impaired host immunity to pathogenic molds - Tappe, Beeke; Lauruschkat, Chris D.; Strobel, Lea; Pantaleón García, Jezreel; Kurzai, Oliver; Rebhan, Silke; Kraus, Sabrina; Pfeuffer-Jovic, Elena; Bussemer, Lydia; Possler, Lotte; Held, Matthias; Hünniger, Kerstin; et al. (Frontiers in Immunology, 2022)
Patients suffering from coronavirus disease-2019 (COVID-19) are at high risk for deadly secondary fungal infections such as COVID-19-associated pulmonary aspergillosis (CAPA) and COVID-19-associated mucormycosis (CAM). Despite this clinical observation, direct experimental evidence for severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2)-driven alterations of antifungal immunity is scarce. Using an ex-vivo whole blood (WB) stimulation assay, we challenged blood from twelve COVID 19 patients with Aspergillus fumigatus and Rhizopus arrhizus antigens and studied the expression of activation, maturation, and exhaustion markers, as well as cytokine secretion. Compared to healthy controls, T-helper cells from COVID-19 patients displayed increased expression levels of the exhaustion marker PD-1 and weakened A. fumigatus- and R. arrhizus-induced activation. While baseline secretion of proinflammatory cytokines was massively elevated, WB from COVID-19 patients elicited diminished release of T-cellular (e.g., IFN-γ, IL-2) and innate immune cell-derived (e.g., CXCL9, CXCL10) cytokines in response to A. fumigatus and R. arrhizus antigens. Additionally, samples from COVID-19 patients showed deficient granulocyte activation by mold antigens and reduced fungal killing capacity of neutrophils. These features of weakened anti-mold immune responses were largely decoupled from COVID-19 severity, the time elapsed since diagnosis of COVID-19, and recent corticosteroid uptake, suggesting that impaired anti-mold defense is a common denominator of the underlying SARS-CoV-2 infection. Taken together, these results expand our understanding of the immune predisposition to post-viral mold infections and could inform future studies of immunotherapeutic strategies to prevent and treat fungal superinfections in COVID-19 patients.